Mapping the landscape of political connections risk: A bibliometric analysis - Widaryanti, Widaryanti; Abdullah, Wan Amalina Wan; Sitawati, Riana; Luhgiatno, Luhgiatno; Tasriastuti, Nurohmi Ambar (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research aims to explain current and future research trends on political connections risk by mapping political connections risk studies.Design/Methodology/Approach: This paper is a meta-synthesis study of the risks of political connections over 25 years, from 2000 to 2024. The Scopus database was used to find relevant literature. Selected articles were scanned, cleaned, and adjusted before analysis. In this analysis, 178 documents were examined. By using biblioshiny, bibliometric analysis in this study gives special emphasis to research flows, trends, thematics, and field structures.Research findings: The bibliometric research results provide essential information about publications on current and future political risks. It includes the most cited documents, prolific contributors, frequently used keywords, prolific countries, sources, network analysis data from co-occurrence networks, and theme mapping data for political relations risk studies. This study identified three main literature clusters: risk assessment, China, and financial crisis. Finally, it raises research questions for future studies. Theoretical contribution/ Originality: This article offers a profound understanding of political connections and risk as a research topic, using bibliometric analysis to examine its academic development. Practitioner/Policy implication: These findings help construct a cohesive idea, define the underlying context, and aid academic researchers and industry practitioners in comprehending the evolution of political connections research and risks.Research limitation/Implication: The sub-themes about the formation and application of political connections and risks, where the number of topics has not been extensively examined, are also anticipated to be expanded by this study.